Macroscopic Modeling of MnZn Ferrites for the Calculation of Eddy-Current Losses in the Frequency- and Time-Domain - Stenglein, Erika; Roßmanith, Hans; Albach, Manfred (19th IEEE Workshop on Control and Modeling for Power Electronics, COMPEL 2018, 2018)
The present trend towards miniaturization of passive components in the field of power electronics requires increased switching frequencies. At higher operating frequencies, however, the eddy-current losses in MnZn ferrites significantly contribute to the energy dissipation, especially in large specimens. This frequency-dependent behavior is correlated to the inhomogeneous micro-structure of the material. Ferrites are composed of grains separated by thin nearly insulating boundary layers. Due to the capacitive behavior of the boundary layers, eddy-currents are not confined within the grains but can flow across the whole sample cross-section.The first part of this paper will identify the contributions to losses of eddy-currents circulating inside the grains and eddy currents circulating within the entire sample cross-section. For this investigation, the microscopic structure of the ferrite is modeled including the individual grains and grain boundaries. Based on the results, formulas for macroscopic material properties are derived, which describe the frequency-dependent behavior of MnZn ferrites. As a characterization of ferrites in the frequency domain is only valid for small excitations, the macroscopic modeling of the material is extended to the time-domain. The derived time-domain model is valid for any excitation. Hence, the heterogeneous structure in combination with the nonlinear and hysteretic magnetic behavior of ferrites can be included in time-domain simulations.
Keywords: Eddy-Current Losses; Macroscopic Modeling; Frequency Domain Simulations; Time Domain Simulations; MnZn Ferrites